ANALISIS FAKTOR PENUNJANG PENGOPTIMALAN KINERJA TERMINAL KABUPATEN KAPUAS - Andrianto Setiawan (Jurnal Teknologi Berkelanjutan, 2018)
The performance of the terminal that has been built by the Kapuas Regency government is still not optimal. Therefore, it is felt necessary to conduct research to identify, compile hierarchies, analyze indicators of influence that have a significant weight in influencing the performance of terminals as well as knowing the location of the most desirable terminals. This study uses cluster analysis methods and Analytical Hierarchy Process (AHP). Through cluster analysis the factors that have a significant effect on improving the performance of the Kapuas Regency Terminal consist of 5 (five) key indicators which are broken down into 20 (twenty) key performance indicators and 10 (ten) clusters with a hierarchical structure namely accessibility, waiting time for departure ( headway), availability of terminal facilities and infrastructure, transportation costs, terminal capacity, terminal environment security, destination and direction of travel, availability of number and type of transportation fleet, traffic flow density and convenience of the terminal environment. The influence indicator which has a significant weight in influencing the performance of the Kapuas Regency Terminal in the existing condition is accessibility with a weight of 13.5% and the location of the terminal and sub-terminal that is most popular is Danumare sub-terminal with a weight of 59.4%. To optimize the performance of the Kapuas Regency terminal, it is necessary to increase accessibility to the terminal location, the accuracy of transport arrival and departure schedules, availability of terminal facilities and infrastructure, competitive transportation costs, terminal capacity, terminal environment security, destination and direction of travel, availability of number and type transport fleet, traffic flow density and the convenience of the terminal environment. The results of AHP after optimization showed an increase in the weight of the performance indicators namely accessibility (31.0%), waiting time for departure / headway (11.9%) and availability of terminal facilities and infrastructure (9.2%) as well as the location of terminals and sub-terminals The most popular are the Kapuas Regency terminal (45.3%), Danumare sub-terminal (29.0%) and the Lotus terminal (25.6%). So, improving the quality of terminal services according to key performance indicators is very influential on improving terminal performance.